Using EEG to Predict Clinical Response to Electroconvulsive Therapy in Patients With Major Depression: A Comprehensive Review - Simon, Louis; Blay, Martin; Galvao, Filipe; Brunelin, Jerome (Frontiers in Psychiatry, 2021)
Introduction. An important approach to improve the therapeutic effect of ECT may be to early characterize patients who are more likely to respond. Our objective was to explore whether baseline EEG settings before the beginning of ECT treatment can predict future clinical response to ECT in patients with depressive disorder. Methods. We conducted a systematic search in the MEDLINE, EMBASE, PsycINFO, Web of Science and Cochrane Central Register of Controlled Trials (CENTRAL) databases to identify studies using EEG in adults with depressive disorder treated by ECT. To investigate the predictive value of baseline EEG on clinical outcomes of ECT, we extracted from the retrieved studies and qualitatively described the association between the baseline EEG markers characteristics and the rates of future responders and/or remitters to ECT. Results. The primary search yielded 2531 potentially relevant citations and 12 articles were selected according to inclusion criteria. Most of the studies were prospective studies with small sample size. Sociodemographic and clinical characteristics of patients, ECT settings, EEG settings and outcomes were heterogeneous. Event-related potential (ERP) paradigms were used in three studies, polysomnography was used in three studies and the 6 other studies used EEG to measure cerebral connectivity and activity. Conclusions. P300 amplitude, coherence and connectivity measures were correlated with remission in patients with depression treated by ECT. Sleep EEG recordings seemed not to be correlated with remission after ECT. Further prospective studies with large sample size are needed to determine optimal EEG parameters associated with clinical response to ECT in depressive disorder. PROSPERO CRD42020181978